Examining the Use of Video Analysis on Teacher Instruction and Teacher Outcomes - Meline, McKenzie; Harn, Beth; Jamgochian, Elisa; Stickland-Cohen, M. Kathleen; Linan-Thompson, Sylvia; Lucero, Audrey (The Journal of special education, 2023)
The purpose of this meta-analysis was to examine the literature base of single-case research design studies using video analysis to determine its effectiveness on teacher outcomes. Primary, ancestral, citation, and first author searches identified 12,047 dissertations and peer-reviewed articles published from 2010 to 2020. Each study (n = 24) was scored on its adherence to the What Works Clearinghouse design quality standards. A total of 16 articles were reviewed for statistical analysis, in which a between-case standardized mean difference was used to calculate effect sizes. Results indicate praise (n = 6; g = 2.66–0.37) and implementation (n = 6; g = 3.64–1.07) had effect sizes that continue to define video analysis as a promising practice. Recommendations for future practice include improving the methodological rigor of studies and increasing sample size to prove the generalizability of video analysis. Addressing these recommendations will support video analysis becoming an evidence-based practice (EBP) for educator development.